Histomorphometric Analysis of Callus Formation Stimulated by Axial Dynamisation in a Standardised Ovine Osteotomy Model. (12th February 2019) - Reich, K. M.; Tangl, S.; Heimel, P.; Lettner, S.; Ignatius, A.; Claes, L. E.; Pfeil, J.; Janousek, A.; Redl, H.
Abstract : The cyclic axial dynamisation of a stabilised fracture is intended to promote callus formation and bone healing. Most studies focused on biomechanical properties or the quantity of new bone formation. Far less is known about the quality of newly formed callus tissues, such as tissue distribution and arrangement within the callus. The aim of this current study was to investigate the effect of cyclic, axial dynamisation on the quantity and quality of callus in an established delayed fracture healing model. In 41 sheep transverse osteotomies with a gap size of 3 mm were stabilised with a unilateral external fixator. In 32 of these, fracture ends were axially stimulated with displacement amplitudes of 0.8 mm, 0.4 mm, 0.2 mm, or 0.0 mm, respectively, for six weeks. In the remaining 9 sheep of the control group, an additional external fixator was mounted to achieve almost total rigidity. Animal material originating from a past animal experiment was reanalysed in this study. Histological thin-ground sections were histomorphometrically analysed regarding the histological structure and composition of the defect region. A slight tendency towards an increase in size of total callus area, area of new bone (nB.Ar), and cartilage (Cg.Ar) was detected with increasing displacement amplitudes compared to the control group. At the anterior callus side nB.Ar and Cg.Ar were significantly larger than at the posterior side in all groups independent of treatment. Regarding the quality of callus, areas of very compact bone were predominant in the treatment groups whereas in the control group a slight shift to more porous bone was observed. No difference of callus compactness was observed between the anterior and the posterior side. The established method to assess the local compactness of callus areas is a useful tool to quantitatively determine the spatial distribution of new bone tissue within the callus. The application of this method in combination with biomechanical testing might reveal interesting relations between tissue distribution and bone strength that, with traditional histomorphometry, cannot be identified.